The Effects of Competition on the Price for Cable Modem Internet Access - Chen, Yongmin; Savage, Scott J (The Review of Economics and Statistics, 2011)
Theory suggests that a firm facing competition will raise prices as consumer preferences become more diverse, and with high enough diversity, a duopolist under product differentiation may price higher than a monopolist. Focusing on the price for cable modem Internet access, with or without DSL competition, and using the standard deviation of education attainment as a proxy for preference diversity, we find empirical support for these results. In markets where cable competes with DSL, the cable Internet price increases with preference diversity. Moreover, the cable Internet price under DSL competition can exceed that without competition when preferences are sufficiently diverse. © 2011 The President and Fellows of Harvard College and the Massachusetts Institute of Technology.